The Food-Contaminant Deoxynivalenol Modifies Eating by Targeting Anorexigenic Neurocircuitry - Girardet, Clémence (Public Library of Science, 2011)
Physiological regulations of energy balance and body weight imply highly adaptive mechanisms which match caloric intake to caloric expenditure. In the central nervous system, the regulation of appetite relies on complex neurocircuitry which disturbance may alter energy balance and result in anorexia or obesity. Deoxynivalenol (DON), a trichothecene, is one of the most abundant mycotoxins found on contaminated cereals and its stability during processing and cooking explains its widespread presence in human food. DON has been implicated in acute and chronic illnesses in both humans and farm animals including weight loss. Here, we provide the first demonstration that DON reduced feeding behavior and modified satiation and satiety by interfering with central neuronal networks dedicated to food intake regulation. Moreover, our results strongly suggest that during intoxication, DON reaches the brain where it modifies anorexigenic balance. In view of the widespread human exposure to DON, the present results may lead to reconsider the potential consequences of chronic DON consumption on human eating disorders.